Data analytics: effective methods for presenting results - Samaddar, Subhashish (Data Analytics Applications., 2019)
"Effective presentation of analytical results is the key to close a project successfully. With the meteoric rise in the popularity of data science and analytics, business executives focus on analytics' strategic interpretation and managerial implications, as well as value creation from analytics. One of the major challenges faced by analytics specialists is to be able to present and communicate the results of their analyses in business terms. With this book, readers learn the strategies of effectively communicating and presenting quantitative analytical results to their clients and senior management"--